Correlation between latent myofascial trigger point and peak torque production of lower limb muscles on sports person - Das, R.; Jhajharia, B. (Journal of Physical Education and Sport, 2022)
Introduction: Latent Myofascial Trigger point is a musculoskeletal disorder and a component of myofascial pain syndrome. The literature suggests Myofascial Pain syndrome should be considered a potential cause of musculoskeletal pain. In the field of sports and exercise, it was found that musculoskeletal injuries are the most common and evidence supports sports persons develop myofascial pain syndrome. This musculoskeletal disorder is a barrier to sports performance. According to the literature, Latent Myofascial Trigger Points decreased force production, but this concept requires further investigation. Moreover, no study has been conducted on force production and lower limb muscles. Purpose: The objective of this study was to investigate the relationship between Latent Myofascial Trigger Points and force production in the lower limb muscles. Thus, it was hypothesized that there would be a significant positive correlation between Latent Myofascial Trigger points and force production in lower limb muscles in athletes. Materials and methods. There were 46 male national-level athletes selected for this study. Total 23 subjects (20.87±2.13 years; height:160.10±5.91; weight:52.40±5.55) were found with Latent Myofascial Trigger Point (Group-1) and 23 subjects (20.45±2.18 years; height:160±5.66; weight:59.80±5.81) were selected non-Latent Myofascial Trigger Point (Group 2). A pressure algometer was used to assess Latent Myofascial Trigger Points (FPX 25 Wagner Instruments, Greenwich, CT, USA) with the mean value of pain pressure threshold and muscular strength was measured by HUMAC NORM ISOKINETIC (Computer Sports Medicine, Inc. Stoughton, MA, USA) with the mean value of peak torque. In descriptive statistics, mean and standard deviation were used, and Pearson correlation was used to determine the relationship between the variables. The level of significance was set at 0.05. Results. A significant positive correlation was found between Latent Myofascial Trigger Points and lower limb force production (p < 0.05). Conclusion. Therefore, it was concluded that Latent Myofascial Trigger Points decreased muscular strength and negatively affect sports performance. Thus, Latent Myofascial Trigger Point should be considered a serious musculoskeletal disorder and proper preventive measures should be taken by health professionals.